Evaluation of pharmacological activities and assessment of intraocular penetration of an ayurvedic polyherbal eye drop (Itone™) in experimental models - Velpandian Thirumurthy; Gupta Pankaj; Ravi Alok Kumar; Sharma Hanuman Prasad; Biswas Nihar Ranjan (BMC, 2013)
Abstract Background The polyherbal eye drop (Itone™) is a mixture of aqueous distillates of nineteen traditionally used ingredients that sum up to impart potency to the formulation and make it a useful adjunct in various ocular pathologies. However, as there have been no controlled experimental studies accounting to the above claim, therefore, the present study was designed to evaluate the polyherbal formulation (PHF) for antiangiogenic, anti-inflammatory, anticataract, antioxidant and cytotoxicity in addition to the evaluation of intraocular penetration of PHF in rabbit eyes using LC-MS/MS. Materials and methods Antiangiogenic activity of the PHF was evaluated using in ovo chick chorio-allantoic membrane (CAM) assay and in vivo cautery induced corneal neovascularization assay in rats. Anticataract potential was evaluated using steroid induced cataract in developing chick embryos, sodium selenite induced cataract in rat pups and galactose induced cataract in rats. The antioxidant activity was evaluated using di-phenyl picryl hydrazyl (DPPH) radical scavenging assay. Anti-inflammatory activity was evaluated in vitro using inhibition of LTB4 formation in human WBCs and in vivo using carrageenan induced paw edema assay in rats. The cytotoxicity was evaluated against HeLa cancer cell lines using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Furthermore evaluation of the intraocular penetration of the PHF was carried out in rabbit eyes via aqueous humor paracentesis and further analysis using LC-MS/MS. Results PHF significantly inhibited VEGF induced proliferation of new blood vessels in CAM assay and inhibited the cautery induced corneal neovascularization in rats. Additionally, PHF showed noticeable delay in the progression of cataract in the selenite and galactose induced cataract models whereby the PHF treated lenses were graded for stages II and III respectively. However, the PHF did not show any anticataract activity in the hydrocortisone induced cataract model. Moreover, PHF exhibited anti-inflammatory activity whereby it showed 39.34% inhibition of LTB4 formation and significantly inhibited carrageenan induced paw edema in rats. Eight compounds of PHF viz. camphor, casticin, curcumin-II, quercetin, rosmarinic acid, γ-terpinene, β-pinene and dipentene exhibited transcorneal penetration in rabbit eyes. Conclusion The significant antiangiogenic and anti-inflammatory activities evinced by the PHF merits further investigation for ocular neovascular and inflammatory diseases in humans.